Historical and Cultural Sources of Pedagogical Project, The Importance of Projecting in The Military Education System - Lieutenant Colonel B. A. Ismatov (Scientific Trends, 2024)
This article focuses on the reform of the educational system, pedagogical project, and its historical and cultural sources, which are becoming relevant today. The structural components, types, content of the project are revealed. Some aspects of planning in the military education system, on the example of the military academic lyceum, were analysed.
Keywords: Academic lyceum, education, design, object, subject, profession.